Number theory ultimatum by Rohith, Anirudh and Arjun!

a 2 + b 2 + c 2 = 2 ( a + b + c + 1 ) a^{2} + b^{2} + c^{2} = 2(a+b+c+1) and
a b + b c + c a = a 2 + b 2 + c 2 c ab+bc+ca = a^{2} + b^{2} + c^{2} - c

Let a , b , c a, b, c are positive integers which satisfy the equations above, find a + b + c a + b + c .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Equation 1 can be factorised into (a-1)^2 + (b-1)^2 +(c-1)^2= 5. From here it is trivial that a,b,c are 1,2,3

main bhi yehi kiya... it's simple method if provided they (a,b and c) are integers!

Sarthak Rath - 5 years, 11 months ago
Akash Deep
Jun 8, 2015

Put the value of a 2 + b 2 + c 2 a^{2} + b^{2} + c^{2} from equation 1 in eq. 2 we get;- a b + c ( a + b ) = 2 ( a + b ) + c + 2 ab + c(a + b) = 2(a + b) + c + 2 this furher can be written as; a b + ( c 2 ) ( a + b 1 ) = 4 ; a b < = 4 ab + (c - 2)(a + b - 1) = 4 ; ab <= 4 from equation 1 we see that two of a,b,c are odd and one even. Or all even so for ab = 4 , a = 2 , b =2 . and this doesn't satisfy the first equation. Similar manipulation for ab = 1 and 3 gives no solution . For ab = 2 , a = 1 and b = 2 and this also gives c = 3. This is a consistent solution as it satisfies both the equations therefore ( a + b + c ) = 6 (a + b + c) = \boxed{6}

could you please try to give a more detailed manner for solving this question. Although your solution is not wrong it doesn't seem to be encompassing.

Anirudh Chandramouli - 5 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...